Uncovering ‘Hidden’ Signals: Previously Presumed Visual Signals Likely Generate Air Particle Movement - Kundu, Pallabi; Choi, Noori; Rundus, Aaron S.; Santer, Roger D.; Hebets, Eileen A. (Frontiers in Ecology and Evolution, 2022)
Wolf spiders within the genus Schizocosa have become a model system for exploring the form and function of multimodal communication. In terms of male signaling, much past research has focused on the role and importance of dynamic and static visual and substrate-borne vibratory communication. Studies on S. retrorsa, however, have found that female-male pairs were able to successfully mate in the absence of both visual and vibratory stimuli, suggesting a reduced or non-existent role of these signaling modalities in this species. Given these prior findings, it has been suggested that S. retrorsa males may utilize an additional signaling modality during courtship—air particle movement, often referred to as near-field sound—which they likely produce with rapid leg waving and receive using thin filiform sensory hairs called trichobothria. In this study, we tested the role of air-particle movement in mating success by conducting two independent sets of mating trials with randomly paired S. retrorsa females and males in the dark and on granite (i.e., without visual or vibratory signals) in two different signaling environments—(i) without (“No Noise”) and (ii) with (“Noise”) introduced air-particle movement intended to disrupt signaling in that modality. We also ran foraging trials in No Noise/Noise environments to explore the impact of our treatments on overall behavior. Across both mating experiments, our treatments significantly impacted mating success, with more mating in the No Noise signaling environments compared to the Noise environments. The rate of leg waving—a previously assumed visual dynamic movement that has also been shown to be able to produce air particle displacement—was higher in the No Noise than Noise environments. Across both treatments, males with higher rates of leg waving had higher mating success. In contrast to mating trials results, foraging success was not influenced by Noise. Our results indicate that artificially induced air particle movement disrupts successful mating and alters male courtship signaling but does not interfere with a female’s ability to receive and assess the rate of male leg waving.